Enhanced UV stability of N-halamine-immobilized Fe3O4@SiO2@TiO2 nanoparticles: synthesis, characteristics and antibacterial property. (9th June 2020) - Bu, Danlin; Li, Na; Zhou, Yu; Feng, Hengyu; Yu, Fei; Cheng, Chunxia; Li, Ming; Xiao, Linghan; Ao, Yuhui
Abstract : Recycling of N -halamine-modified Fe3 O4 @SiO2 @TiO2 antibacterial materials with UV stability. Abstract : N -Halamine-based antibacterial materials are widely used due to their excellent characteristics. However, the N–Cl bonds in N -halamine-based materials are not stable under UV light irradiation so that they are difficult to recover and reuse. Here, a kind of N -halamine-immobilized Fe3 O4 @SiO2 @TiO2 (F@S@T-Cl) nanoparticles were prepared. In addition, the UV stability and regeneration capacity were also studied after variable time exposure to UV light. The results showed that nanoparticles have great antibacterial properties against Staphylococcus aureus and Escherichia coli . Meanwhile, the N–Cl bond in the nanocomposite showed outstanding storage stability under UV light irradiation and good regeneration ability; the material can realize cyclic utilization and solve the problem of secondary pollution of the antibacterial material. It provides a broader application prospect for the recyclable N -halamine antibacterial material.